Correlation between Gross Motor Function Classification System and Communication Function Classification System in Children with Cerebral Palsy - Margaretha, Vindy; Prananta, Marietta Shanti; Alam, Anggraini (Althea Medical Journal, 2017)
Background: Cerebral Palsy (CP) is a group of movement and posture disorder commonly accompanied by comorbidities such as sensation, cognition, communication abnormalities and many more. This study aimed to identify the correlation between gross motor function(measured by Gross Motor Function Classification System, GMFCS) and communication function (measured by Communication Function Classification System, CFCS) in children with CP.Methods: Thirty six children with CP aged 0â12 years were examined. Samples were taken from Department of Physical Medicine and Rehabilitation Dr. Hasan Sadikin General Hospital Bandung on September to October 2015. Patientsâ descriptive data, levels of GMFCS and CFCS were collected by the researcher and residents previously standardized. Kendallâs tau b correlation coefficient was used to analyze the inter-relationship between the GMFCS and CFCS.Results: Levels of GMFCS and CFCS in all samples were moderately correlated (r=0.405; p=0.004). In patients with spastic quadripledic type, correlation were found moderate(r=0.495; p=0.014). No significant correlation was found when CP spastic quadriplegic patients were excluded (r=0.048, p=0.829).Conclusions: Levels of GMFCS and CFCS should be described to provide the complete gross motor and communication picture of CP children.Gross motor function in a child with spastic quadriplegic CP might be correctly predicted from his/ her communication function and vice versa.Â DOI:Â 10.15850/amj.v4n2.1092